Rural Education teachers and resistance: the breaches in teaching habitus - Hildete Pereira Anjos; Débora dos Reis Cordeiro (Universidade Federal do Norte do Tocantins, 2021)
This work analyzes teaching practices which refer to resistance in teaching habitus. We carried out a case study involving teachers graduated in the first classes of the Rural Education degree course. We assume that a student graduation engaged in the rural education struggles must train teachers whose teaching practices escapes the education structuring habitus in general, producing resistance also in the pedagogical field. The results point to the production of ways of resistance through tactics in which they improvise in the shortage of necessary materials and equipment; in which they share the little they have and make it a reason for reflection; in which they problematize the lived situations in daily life by teachers and students and make this a material and pedagogical activity; in which they redesign the circular distribution of students in the class and make the dynamics of relations break the linearity. In contrast, the rigid way in which education is organized as a whole - which is a strong component of the habitus - keeps framing/limiting initiatives, pointed to the constant need to problematize the curriculum, school times and social places occupied by the school and teachers.